Gestión turística municipal y el desarrollo sostenible de la provincia de Maynas 2022 - Arévalo Sandi, Ericka Lizbeth (2024)
A study was carried out whose main objective was to determine the relationship between municipal tourism management and sustainable development in the province of Maynas, 2022. The research was based on a descriptive and correlational approach, in which the data were analyzed and described. collected, it is worth mentioning that the design used was not experimental; The study focused on a population of 550,551 residents, of which 384 were chosen to participate in a survey in conjunction with a questionnaire, in order to obtain the desired information. Obtaining as results, where the tourism management carried out by the municipality is classified as deficient (45%); while sustainable development is rated as low (42%). Therefore, it has been determined that there is a considerable positive relationship between municipal tourism management and sustainable development contrasted by a coefficient and a sig. of r=0.852; p=0.000; Likewise, a positive and significant relationship is established between municipal tourism management planning, demonstrated by an index of 0.377 and a sig. of 0.000; The organizational dimension of municipal tourism management has a coefficient of 0.603 and a sig. of 0.000; also, direction of municipal tourism management a coefficient of 0.762 and a sig. of 0.000; and the control of municipal tourism management an index of 0.560 and a sig. of 0.000, both dimensions are positively and significantly related to the sustainable development of the province of Maynas, in 2022.